The Effect of PjBL-Based QODE Model on Critical Thinking and Learning Achievement of Buffer Solution Topic - Wulayalin, Khafifah Aulia; Zamhari, Muhammad; Ramadanti, Wicahni; Nurjanah, Stevani (IJCER (International Journal of Chemistry Education Research), 2025)
Chemical misconceptions often occur when students need to understand the initial concept. This misconception has an impact on students' ability to understand the material and results in a decrease in students' learning achievement. Students' concept understanding can significantly improve by applying practical learning approaches, models, and strategies. This study aims to determine how applying the QODE learning model based on PjBL improves grade XI students' learning achievement and critical thinking skills on Buffer Solution topic. This type of research is a quasi-experiment with a nonequivalent control group pretest–posttest design. This study's subjects were control class for cooperative learning group investigation learning model and experimental class for PjBL-based QODE learning model at SMA Negeri 1 Sleman. Two intact classes (n = 36 per group) completed a two-tier multiple-choice critical-thinking test and an achievement test before and after a 3-session intervention. The research data were analyzed using the Wilcoxon and the N-gain tests. The Wilcoxon test result shows that both learning models used in experimental and control groups influence student learning achievement and critical thinking with the value of Sig. <0.05. N-Gain test shows that the experimental group experienced an increase of 0.74 for critical thinking skills and 0.78 for student learning achievement which in high category, while the control group experienced an increase of 0.38 for critical thinking skills and 0.73 for student learning achievement which in low and high category. These findings indicate that the QODE learning model based on PjBL contributes to improving students' critical thinking.